Distal limb deficiencies, micrognathia syndrome, and syndromic forms of split hand foot malformation (SHFM) are caused by chromosome 10q genomic rearrangements. Issue 2 (6th July 2009) - Dimitrov, B I; de Ravel, T; Van Driessche, J; de Die-Smulders, C; Toutain, A; Vermeesch, J R; Fryns, J P; Devriendt, K; Debeer, P
Abstract : Background: The 10q24 chromosomal region has previously been implicated in split hand foot malformation (SHFM). SHFM3 was mapped to a large interval on chromosome 10q. The corresponding dactylaplasia mouse model was linked to the syntenic locus on chromosome 19. It was shown that the two existing Dac alleles result from MusD-insertions upstream of or within Dactylin ( Fbxw4 ). However, all efforts to find the underlying cause for the human SHFM3 have failed on the analysis of all the genes within the linkage region. Intriguingly a submicroscopic duplication within the critical locus on chromosome 10q24 was associated with the phenotype. Methods and results: As a part of screening for genomic rearrangements in cases with unexplained syndromic limb defects, a cohort of patients was analysed by array comparative genomic hybridisation (CGH). A 10q24 microduplication was detected in two individuals with distal limb deficiencies associated with micrognathia, hearing problems and renal hypoplasia. In addition, in a family with two affected siblings, a somatic/gonadal mosaicism for the microduplication was detected in the apparently healthy mother. Using a high resolution oligoarray further delineation of the duplication size was performed. Conclusions: The detected 10q24 genomic imbalance in our syndromic patients has a similar size to the duplication in the previously reported individuals with an isolated form of SHFM, thus extending the clinical spectrum of SHFM3. These findings clearly demonstrate the importance of array CGH in the detection of the aetiology of complex, clinically heterogeneous entities.